Sexual offences committed by members of the armed forces: Is the service justice system fit for purpose? - Herriott, Charlotte (Criminology & criminal justice, 2025)
Recent policy reviews, academic research and high-profile media critiques have repeatedly emphasised the UK military as a hypermasculine culture, seemingly permissive of sexual violence, marked by high prevalence of sexual offences and an inadequate justice response. The service justice system has been characterised by low conviction rates and poor treatment of victim-survivors of sexual offences, prompting recommendation that rape should be tried in the civilian criminal justice system rather than the service justice system. Despite notable debate on this matter, the Ministry of Defence (MOD) ultimately rejected this recommendation in December 2021 and instead committed to implementing clear and meaningful change within the service justice system response to sexual offences. In light of this decision, this article interrogates available data about the current service justice system response to sexual offending, and lessons that may be learnt from the civilian criminal justice system, to highlight current obstacles to justice and outline areas in which further research and scrutiny is necessary.